Effects of Propionyl-L-Carnitine on Ischemia–Reperfusion Injury in Hamster Cheek Pouch Microcirculation - Lapi, Dominga; Sabatino, Lina; Altobelli, Giovanna G.; Mondola, Paolo; Cimini, Vincenzo; Colantuoni, Antonio (Frontiers in Physiology, 2010)
Background and Purpose Propionyl-L-carnitine (pLc) exerts protective effects in different experimental models of ischemia-reperfusion (I/R). The aim of the present study was to assess the effects of intravenously and topically applied pLc on microvascular permeability increase induced by I/R in the hamster check pouch preparation. Methods The hamster check pouch microcirculation was visualized by fluorescence microscopy. Microvascular permeability, leukocyte adhesion to venular walls, perfused capillary length and capillary red blood cell velocity (VRBC) were evaluated by computer-assisted methods. E-selectin expression was assessed by in vitro analysis. Lipid peroxidation and reactive oxygen species (ROS) formation were determined by thiobarbituric acid-reactive substances (TBARS) and 2’-7’-dichlorofluorescein (DCF), respectively. Results In control animals, I/R caused a significant increase in permeability and in the leukocyte adhesion in venules. Capillary perfusion and VRBC decreased. TBARS levels and DCF fluorescence significantly increased compared with baseline. Intravenously infused pLc dose-dependently prevented leakage and leukocyte adhesion, preserved capillary perfusion and induced vasodilation at the end of reperfusion, while ROS concentration decreased. Inhibition of nitric oxide synthase prior to pLc caused vasoconstriction and partially blunted the pLc-induced protective effects; inhibition of the endothelium-derived hyperpolarizing factor (EDHF) abolished pLc effects. Topical application of pLc on check pouch membrane produced the same effects as observed with intravenous administration. pLc decreased the E-selectin expression. Conclusions pLc prevents microvascular changes induced by I/R injury. The reduction of permeability increase could be mainly due to EDHF release induce vasodilatation together with NO. The reduction of E-selectin expression prevents leukocyte adhesion and permeability increase.